Analisis Kepuasan Mahasiswa Terhadap Ketersediaan Sarana Dan Prasarana Laboratorium - Rozalinda, Kelly; Syevyilni Wisda, Rini; Nurzen.S, M. (JURUSAN MANAJEMEN PENDIDIKAN FAKULTAS ILMU PENDIDIKAN UNIVERSITAS NEGERI GORONTALO, 2025)
Higher education has an important role in forming a competent and competitive young generation, however, student perceptions of infrastructure facilities play an important role in the availability and feasibility of facilities including the availability of laboratory infrastructure. This study analyzes the perceptions of students majoring in Biology on the availability of laboratory facilities IAIN Kerinci. This research is a survey research, informants are all students majoring in Biology IAIN Kerinci, the research instrument is designed online with google form, the data is analyzed descriptively quantitative. The results showed that. The results of research on student satisfaction with laboratory facilities and infrastructure at IAIN Kerinci showed the majority of students gave a positive assessment. However, there are aspects that need to be improved, such as the adequacy of tools and materials, ease of access, information support, and the availability and willingness of instructors. A thorough evaluation and appropriate improvements are needed to improve the quality of students' learning experience in conducting research and practicum in the laboratory.